2017
DOI: 10.15740/has/au/12.techsear(1)2017/259-264
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bemisia tabaci Gennadiu on Bt cotton ecosystem in Marathwada region of Maharashtra

Abstract: The severity whitefly is becoming a major concern to transgenic cotton farmers. Keeping this in view scientific survey of white fly (Bemisia tabaci Gennadius) incidence on Bt cotton was carried out from last five years (2009-10 to 2013-14), in six major cotton growing districts (viz. Parbhani, Hingoli, Nanded, Jalna, Aurangabad & Beed) in Marathwada region of Maharashtra under Crop Pest Surveillance and Advisory Project (CROPSAP) by using ICT tools and total 171 ETL based advisories were issued twice in a week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Leafhopper infestation showed positive correlation with morning relative humidity and negative correlation with maximum and minimum temperature, evening relative humidity and rainfall in Bt-cotton and non-Bt cotton. Badgujar et al (2015) found that among BG-I minimum jassid population was recorded on ACH-21-1-BG-I which was found significantly superior over rest of BG-I hybrids while maximum jassid population was recorded on RCH-2 BG-I. Among BG-II, minimum jassids population was recorded on ACH-155 and maximum jassids population was recorded on RCH-2 BG-II.…”
Section: Population Dynamic Of Cotton Leafhopper Amrasca Devastansmentioning
confidence: 82%
“…Leafhopper infestation showed positive correlation with morning relative humidity and negative correlation with maximum and minimum temperature, evening relative humidity and rainfall in Bt-cotton and non-Bt cotton. Badgujar et al (2015) found that among BG-I minimum jassid population was recorded on ACH-21-1-BG-I which was found significantly superior over rest of BG-I hybrids while maximum jassid population was recorded on RCH-2 BG-I. Among BG-II, minimum jassids population was recorded on ACH-155 and maximum jassids population was recorded on RCH-2 BG-II.…”
Section: Population Dynamic Of Cotton Leafhopper Amrasca Devastansmentioning
confidence: 82%